Electrochemical device, preparation method and electronic device

By using a combination of positive electrode active material and expanded graphite on the positive electrode sheet of the electrochemical device, the ratio of through-holes and non-through holes is controlled, and the problems of high cost and safety risks of improving the dynamic performance of existing electrochemical devices are solved, achieving more efficient lithium ion transmission and lower resistance.

CN119764327APending Publication Date: 2025-04-04NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411957316.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing electrochemical devices have high costs, easy damage to the positive electrode current collector and increase resistance in improving kinetic performance, which affects the transmission rate of lithium ions and the safety of the electrochemical devices.

Method used

A positive electrode sheet is designed, which includes a positive electrode current collector and a positive electrode material layer disposed on its surface. The positive electrode material layer is composed of a positive electrode active material and expanded graphite. By regulating the number and proportion of through holes and non-through holes, 0.4≤n/N≤0.75 is ensured to improve the transmission path and contact area of ​​lithium ions.

Benefits of technology

By increasing the transmission path of lithium ions and reducing transmission resistance, the embedded and disengagement speed of lithium ions is improved, the dynamic performance of the electrochemical device is improved, and internal resistance and safety hazards are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216641170000181
    Figure BDA0005216641170000181
  • Figure BDA0005216641170000191
    Figure BDA0005216641170000191
Patent Text Reader

Abstract

The invention provides an electrochemical device, a preparation method and an electronic device, the electrochemical device comprises a positive electrode plate, the positive electrode plate comprises a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode material layer comprises a positive electrode active material and expanded graphite; the sum of the number of the through holes and the non-through holes in the unit square centimeter of the positive electrode material layer far away from the surface of the positive electrode current collector is N, the number of the through holes in the positive electrode material layer is n, and n / N is larger than or equal to 0.4 and smaller than or equal to 0.75. The pores are prepared in the positive electrode material layer through the expanded graphite, a transmission path is provided for lithium ions, the diffusion distance is shortened, the transmission resistance is reduced, and meanwhile polarization is reduced; the positive pole piece meets the characteristics, the electrolyte can easily permeate the positive pole material layer, the contact area of the electrolyte and the positive pole material layer is increased, the lithium deintercalation uniformity and rate of the positive pole piece are improved, and the lithium ion transmission rate is further improved. Therefore, the dynamic performance of the electrochemical device comprising the positive pole piece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device, a preparation method and an electronic device. Background Art

[0002] Electrochemical devices (such as lithium-ion batteries) have the advantages of high energy density, long cycle life, low self-discharge rate and environmental protection and pollution-free. They have been widely used in aviation, aerospace, navigation, electric vehicles and other fields.

[0003] With the widespread use of electrochemical devices, people's demand for their dynamic performance is growing. At present, in electrochemical devices, the pores of the positive electrode sheet are mainly focused on the surface of the positive electrode sheet by a high-energy laser beam. The high heat causes the positive electrode material layer in the target area to undergo a phase change and leave holes, thereby improving the dynamic performance of the electrochemical device. However, laser pore making is costly and easy to damage the positive electrode collector, which increases the resistance of the electrochemical device, thereby reducing the conductivity of the positive electrode sheet and affecting the current transmission rate; at the same time, it may also cause the positive electrode material layer to fall off from the positive electrode collector, or the positive electrode collector to contact the negative electrode, causing an internal short circuit in the electrochemical device and causing thermal runaway, posing a safety hazard. Summary of the invention

[0004] The purpose of the present application is to provide an electrochemical device, a preparation method and an electronic device to improve the kinetic performance of the electrochemical device.

[0005] The first aspect of the present application provides an electrochemical device, which includes a positive electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material and expanded graphite; the number of through holes and non-through holes in the surface of the positive electrode material layer away from the positive electrode current collector per square centimeter is N, the number of through holes in the positive electrode material layer is n, and the following is satisfied: 0.4≤n / N≤0.75. The electrochemical device includes the above-mentioned positive electrode plate, and the through holes and non-through holes in the positive electrode material layer can provide more transmission paths for lithium ions, shorten the diffusion distance of lithium ions from the electrolyte to the inside of the positive electrode material layer, and reduce the lithium ion transmission resistance, reduce polarization, and enable lithium ions to be quickly and evenly embedded in and out of the positive electrode material layer, thereby increasing the transmission rate of lithium ions and improving the kinetic performance of the electrochemical device.

[0006] In one embodiment of the present application, the pore size of the positive electrode material layer is 100 μm to 200 μm. The pore size of the positive electrode material layer is within the range of the present application, which further improves the lithium ion transmission rate and the kinetic performance of the electrochemical device.

[0007] In one embodiment of the present application, 2≤N≤12, preferably 6≤N≤12. The positive electrode sheet meeting the above characteristics further improves the kinetic performance of the electrochemical device.

[0008] In one embodiment of the present application, the porosity of the positive electrode material layer is 20% to 35%. By adjusting the porosity of the positive electrode material layer within the scope of the present application, the rate of lithium deintercalation of the positive electrode material layer can be increased, which is beneficial to increase the lithium ion transmission rate, further improve the kinetic performance of the electrochemical device, and take into account the energy density of the electrochemical device.

[0009] In one embodiment of the present application, the maximum thickness of the positive electrode material layer is H, and the average pore depth is h, which satisfies: 0.5≤h / H≤0.9. By adjusting the value of h / H within the scope of the present application, the average pore depth of the positive electrode material layer is increased, providing more transmission paths for lithium ions; at the same time, the contact area between the electrolyte and the positive electrode material layer is increased, and the uniformity and rate of lithium insertion and extraction of the positive electrode sheet are improved, which is conducive to improving the lithium ion transmission rate and further improving the kinetic performance of the electrochemical device.

[0010] In one embodiment of the present application, the mass percentage of expanded graphite in the positive electrode material layer is X1, 0.01%≤X1≤0.25%. The positive electrode sheet meeting the above characteristics has a porous structure, which is conducive to increasing the lithium ion transmission rate and further improving the kinetic performance of the electrochemical device.

[0011] In one embodiment of the present application, the positive electrode plate meets at least one of the following conditions: (1) the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate; (2) the positive electrode material layer includes a binder, and the binder is selected from at least one of polyvinylidene fluoride, polyacrylonitrile, and polyimide. The positive electrode plate meeting the above characteristics further improves the cycle performance of the electrochemical device.

[0012] In one embodiment of the present application, the positive electrode sheet satisfies at least one of the following conditions: (1) the coating weight of the positive electrode material layer on one side is 200 mg / 1540.25 mm 2 Up to 600mg / 1540.25mm 2 , preferably 200mg / 1540.25mm 2 Up to 500mg / 1540.25mm 2 ; (2) The compaction density of the positive electrode material layer is 3.5g / cm 3 Up to 4.5g / cm 3 , preferably 4.1 g / cm 3 Up to 4.3g / cm 3 The positive electrode sheet that meets the above characteristics further improves the kinetic performance, cycle performance and energy density of the electrochemical device.

[0013] In one embodiment of the present application, the DC internal resistance of the electrochemical device at 25° C. and 80% SOC for 360 s at 1C discharge is 30 mΩ to 60 mΩ. An electrochemical device that meets the above characteristics indicates that it has good kinetic performance.

[0014] The second aspect of the present application provides a method for preparing the electrochemical device described in the first aspect of the present application, which includes the steps of preparing the positive electrode sheet: S1, mixing the positive electrode active material, the conductive agent, the binder, and the expanded graphite, adding the solvent and stirring evenly to obtain the positive electrode slurry; S2, applying the positive electrode slurry on one surface of the positive electrode collector, and heat treating it at a temperature range of 120°C to 350°C to obtain the positive electrode material layer; S3, repeating the above steps on the other surface of the positive electrode collector, and obtaining the positive electrode sheet through cold pressing, cutting, and welding processes. The electrochemical device that meets the above positive electrode sheet preparation method has good dynamic performance.

[0015] In one embodiment of the present application, before heat treatment, the mass percentage of expanded graphite in the positive electrode material layer is X2, 0.05%≤X2≤1%. By adjusting X2 within the scope of the present application, the porosity of the positive electrode plate after heat treatment can be improved, which is beneficial to increase the lithium ion transmission rate and further improve the kinetic performance of the electrochemical device.

[0016] The third aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect of the present application or the electrochemical device prepared according to the preparation method described in the second aspect of the present application. Therefore, the electronic device of the present application has good dynamic performance.

[0017] Beneficial effects of this application:

[0018] The present application provides an electrochemical device, which includes a positive electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material and expanded graphite; the number of through holes and non-through holes in a unit square centimeter on the surface of the positive electrode material layer away from the positive electrode current collector is N, and the number of through holes in the positive electrode material layer is n, which satisfies: 0.4≤n / N≤0.75. The present application prepares pores in the positive electrode material layer by expanded graphite, which can provide more transmission paths for lithium ions, shorten the diffusion distance of lithium ions from the electrolyte to the inside of the positive electrode material layer, and reduce the lithium ion transmission resistance and polarization at the same time, so that lithium ions can be quickly and evenly embedded in and out of the positive electrode material layer, thereby improving the transmission rate of lithium ions; the positive electrode plate meets the above characteristics, and can also make the electrolyte more easily penetrate into the positive electrode material layer, increase the contact area between the electrolyte and the positive electrode material layer, improve the uniformity and rate of lithium insertion and extraction of the positive electrode plate, and further improve the lithium ion transmission rate. Therefore, the kinetic performance of the electrochemical device including the positive electrode sheet is improved.

[0019] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0021] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0022] The first aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, the positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector, the positive electrode material layer includes a positive active material and expanded graphite; the number of through holes and non-through holes in a unit square centimeter on the surface of the positive electrode material layer away from the positive current collector is N, and the number of through holes in the positive electrode material layer is n, satisfying: 0.4≤n / N≤0.75; in one embodiment of the present application, 2≤N≤12, preferably, 6≤N≤12. For example, N can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or a range consisting of any two of the values; n / N can be 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75 or a range consisting of any two of the values. The through holes and non-through holes in the present application refer to the pore structure formed by expanded graphite as a pore-forming agent in the positive electrode material layer, and the pore size of the pore structure is greater than 30 μm. Specifically, the expanded graphite expands after being heated and drills out of the positive electrode material layer, thereby forming through holes or non-through holes in the positive electrode material layer. It can be understood that part of the expanded graphite drills out of the positive electrode material layer to form a pore structure, and part of the expanded graphite may not drill out of the positive electrode material layer. The through holes and non-through holes in the positive electrode material layer can provide more transmission paths for lithium ions, shorten the diffusion distance of lithium ions from the electrolyte to the inside of the positive electrode material layer, and reduce the resistance to lithium ion transmission, reduce polarization, and enable lithium ions to be quickly and evenly embedded in and out of the positive electrode material layer, thereby improving the transmission rate of lithium ions; it can also make it easier for the electrolyte to penetrate into the positive electrode material layer, increase the contact area between the electrolyte and the positive electrode material layer, improve the uniformity and rate of lithium deintercalation of the positive electrode sheet, and further improve the lithium ion transmission rate. Therefore, the kinetic performance of the electrochemical device including the positive electrode sheet is improved.

[0023] In the present application, holes with a pore size greater than 30 μm are through holes or non-through holes. Through holes are holes through which the surface of the positive electrode collector can be directly observed when the surface of the positive electrode plate is observed under an optical microscope at a magnification of 30-50 times; non-through holes are holes through which the surface of the positive electrode collector cannot be directly observed when the surface of the positive electrode plate is observed under an optical microscope at a magnification of 30-50 times.

[0024] In some embodiments of the present application, the number of through holes in the surface of the positive electrode material layer away from the positive electrode current collector per square centimeter is n, 1≤n≤9; the number of non-through holes in the surface of the positive electrode material layer away from the positive electrode current collector per square centimeter is 3 to 11, and lithium ions near the through holes in the electrochemical device are easier to deintercalate, further improving the kinetic performance.

[0025] In the present application, expanded graphite refers to graphite with an interlayer spacing of 0.35 nm to 0.5 nm.

[0026] In one embodiment of the present application, the pore size of the positive electrode material layer is 100 μm to 200 μm. For example, the pore size of the positive electrode material layer can be 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm or a range consisting of any two of the values. In the present application, the pore size of the positive electrode material layer refers to the diameter of the through hole and / or the non-through hole. The pore size of the positive electrode material layer is within the scope of the present application. On the basis of improving the electronic conductivity, it can provide more transmission paths for lithium ions, thereby shortening the diffusion distance of lithium ions, reducing the transmission resistance, and reducing polarization, so that lithium ions can be quickly and evenly embedded in and out of the positive electrode material layer, thereby improving the transmission rate of lithium ions; it can also make it easier for the electrolyte to penetrate into the interior of the positive electrode material layer, increase the contact area between the electrolyte and the positive electrode material layer, improve the uniformity and rate of lithium deintercalation of the positive electrode sheet, further improve the lithium ion transmission rate, and further improve the kinetic performance of the electrochemical device.

[0027] In one embodiment of the present application, the porosity of the positive electrode material layer is 20% to 35%. For example, the porosity can be 20%, 22%, 25%, 28%, 30%, 32%, 35% or a range consisting of any two of these values. In the present application, the porosity of the positive electrode material layer refers to the volume percentage of all pores in the positive electrode material layer in the positive electrode material layer. By regulating the porosity of the positive electrode material layer within the scope of the present application, the rate of lithium insertion and extraction of the positive electrode material layer can be increased, which is beneficial to increase the lithium ion transmission rate, further improve the kinetic performance of the electrochemical device, and take into account the energy density of the electrochemical device.

[0028] In one embodiment of the present application, the maximum thickness of the positive electrode material layer is H, and the average pore depth is h, satisfying: 0.5≤h / H≤0.9. For example, the value of h / H can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range consisting of any two of these values. In the present application, the average pore depth refers to the average value of the depths of through holes and non-through holes in the thickness direction of the positive electrode material layer. By regulating the value of h / H within the scope of the present application, the average pore depth of the positive electrode material layer is increased, providing more transmission paths for lithium ions; at the same time, the contact area between the electrolyte and the positive electrode material layer is increased, and the uniformity and rate of lithium insertion and extraction of the positive electrode electrode sheet are improved, which is conducive to improving the lithium ion transmission rate, thereby further improving the kinetic performance of the electrochemical device.

[0029] In the present application, the maximum thickness H of the positive electrode material layer is the maximum thickness of the single-sided positive electrode material layer. In some embodiments of the present application, the maximum thickness of the positive electrode material layer is H, 80 μm ≤ H ≤ 150 μm, and the average pore depth is h, 40 μm ≤ h ≤ 75 μm.

[0030] In the present application, "a positive electrode material layer disposed on at least one surface of a positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its thickness direction, or on two surfaces of the positive electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or a partial area of ​​the surface of the positive electrode current collector. This application has no particular limitation, as long as the purpose of this application can be achieved.

[0031] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0032] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm.

[0033] In the present application, the expanded graphite may be a conventional commercially available substance, and there is no particular limitation on its source, as long as the purpose of the present application can be achieved.

[0034] In one embodiment of the present application, the mass percentage of expanded graphite in the positive electrode material layer is X1, 0.01%≤X1≤0.25%. For example, X1 can be 0.01%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.25% or a range consisting of any two of the values. The positive electrode sheet that meets the above characteristics has a porous structure, which is conducive to improving the lithium ion transmission rate, thereby further improving the kinetic performance of the electrochemical device.

[0035] In one embodiment of the present application, the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide or lithium iron phosphate. The present application has no particular restrictions on the mass percentage of the positive electrode active material in the positive electrode material layer, as long as the purpose of the present application can be achieved. Exemplarily, based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material is 95% to 98%. For example, the mass percentage of the positive electrode active material can be 95%, 96%, 97%, 98% or a range consisting of any two of these values.

[0036] In one embodiment of the present application, the positive electrode material layer includes a binder, and the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN) or polyimide (PI). The positive electrode sheet that meets the above characteristics is conducive to improving the bonding force between the positive electrode sheet and the separator, and further improving the cycle performance of the electrochemical device. The present application has no particular restriction on the mass percentage of the binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. Exemplarily, based on the mass of the positive electrode material layer, the mass percentage of the binder is 0.1% to 3%. For example, the mass percentage of the binder can be 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3% or a range consisting of any two of the values.

[0037] In some embodiments of the present application, the positive electrode material layer includes a conductive agent, and the mass percentage of the conductive agent in the positive electrode material layer is X3, 0.7%≤X3≤2%. For example, X3 can be 0.7%, 0.9%, 1%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, or a range consisting of any two of these values. By regulating the mass percentage of the conductive agent within the scope of the present application, the electronic conductivity is improved, which is beneficial to reduce the internal resistance and further improve the kinetic performance of the electrochemical device.

[0038] In some embodiments of the present application, the conductive agent in the positive electrode material layer includes at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black includes at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers include vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials include metal powders and / or metal fibers, specifically, the metal includes at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer includes at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.

[0039] In one embodiment of the present application, the single-sided coating weight of the positive electrode material layer is 200 mg / 1540.25 mm 2 Up to 600mg / 1540.25mm 2 , preferably 200mg / 1540.25mm 2 Up to 500mg / 1540.25mm 2 For example, the coating weight of the positive electrode material layer on one side is 200 mg / 1540.25 mm 2 、250mg / 1540.25mm 2 、300mg / 1540.25mm 2、350mg / 1540.25mm 2 , 400mg / 1540.25mm 2 450mg / 1540.25mm 2 、500mg / 1540.25mm 2 、550mg / 1540.25mm 2 、600mg / 1540.25mm 2 Or it is a range consisting of any two of the values. The positive electrode sheet satisfying the above characteristics is beneficial to improving the kinetic performance of the electrochemical device while taking into account the energy density.

[0040] In one embodiment of the present application, the compaction density of the positive electrode material layer is 3.5 g / cm 3 Up to 4.5g / cm 3 , preferably 4.1 g / cm 3 Up to 4.3g / cm 3 For example, the compaction density of the positive electrode material layer can be 3.5 g / cm 3 、3.7g / cm 3 、3.9g / cm 3 , 4g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 , 4.5g / cm 3 Or a range consisting of any two of the values. The positive electrode sheet that meets the above characteristics can reduce the internal resistance of the positive electrode sheet, which is beneficial to improving the rate performance of the electrochemical device, further improving the specific capacity of the electrochemical device, and improving the cycle performance of the electrochemical device.

[0041] In the present application, the pore size of the positive electrode material layer can be regulated by regulating the compaction density of the positive electrode material layer, the type of expanded graphite added, or the content of expanded graphite released after heating. For example, if the type of expanded graphite added and the content of expanded graphite released after heating are constant, the greater the compaction density of the positive electrode material layer, the smaller the pore size of the positive electrode material layer, and vice versa; if the type of expanded graphite added and the compaction density of the positive electrode material layer are constant, the higher the content of expanded graphite released after heating, the larger the pore size of the positive electrode material layer, and vice versa; if the content of expanded graphite released after heating and the compaction density of the positive electrode material layer are constant, the pore size of the positive electrode material layer is different due to different types of expanded graphite.

[0042] In the present application, the number and N of through holes and non-through holes in the positive electrode material layer away from the positive electrode current collector surface per square centimeter can be regulated by regulating the type, mass percentage and / or compaction density of the expanded graphite added in the positive electrode material layer. Exemplarily, when other conditions remain unchanged, the higher the mass percentage of the expanded graphite added in the positive electrode material layer, the greater the number and N of through holes and non-through holes in the positive electrode material layer away from the positive electrode current collector surface per square centimeter, and vice versa.

[0043] In the present application, the number n of through holes in the positive electrode material layer can be adjusted by adjusting the type, mass percentage and / or compaction density of the expanded graphite added to the positive electrode material layer.

[0044] In the present application, the value of n / N can be adjusted by adjusting the values ​​of n and N respectively, and the method for adjusting n and N is as described above.

[0045] The present application does not particularly limit the method for regulating the porosity of the positive electrode material layer, as long as the purpose of the present application can be achieved. The porosity of the positive electrode material layer is related to the pore size of the positive electrode material layer, the number and sum of through holes and non-through holes of the positive electrode material layer. For example, the porosity of the positive electrode material layer can be regulated by regulating the pore size of the positive electrode material layer, the number and sum of through holes and non-through holes of the positive electrode material layer, and the method for regulating the pore size of the positive electrode material layer, the number and sum of through holes and non-through holes of the positive electrode material layer is as described above. Exemplarily, when the number and sum of through holes and non-through holes of the positive electrode material layer is constant, the larger the pore size of the positive electrode material layer, the higher the porosity of the positive electrode material layer, and vice versa; when the pore size of the positive electrode material layer is constant, the larger the number and sum of through holes and non-through holes of the positive electrode material layer, the higher the porosity of the positive electrode material layer, and vice versa.

[0046] The present application does not particularly limit the method for regulating the maximum thickness H of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the maximum thickness H of the positive electrode material layer can be regulated by regulating the coating weight or compaction density of the positive electrode material layer. Exemplarily, when the coating weight of the positive electrode material layer is constant, the higher the compaction density of the positive electrode material layer, the lower the maximum thickness H of the positive electrode material layer, and vice versa; when the compaction density of the positive electrode material layer is constant, the greater the coating weight of the positive electrode material layer, the higher the maximum thickness H of the positive electrode material layer, and vice versa.

[0047] The present application does not particularly limit the method for regulating the compaction density of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the compaction density of the positive electrode material layer can be regulated by regulating the coating weight and cold pressing pressure of the positive electrode material layer. Exemplarily, when the coating weight of the positive electrode material layer is constant, the higher the cold pressing pressure, the higher the compaction density of the positive electrode material layer, and vice versa; when the cold pressing pressure of the positive electrode material layer is constant, the greater the coating weight of the positive electrode material layer, the higher the compaction density of the positive electrode material layer, and vice versa.

[0048] In the present application, the mass percentage X1 of the expanded graphite in the positive electrode material layer can be regulated by regulating the mass of the expanded graphite in the added positive electrode material layer or the temperature of the heat treatment. Exemplarily, when the mass of the expanded graphite in the added positive electrode material layer is constant, the higher the temperature of the heat treatment, the lower the mass percentage X1 of the expanded graphite in the positive electrode material layer, and vice versa; when the temperature of the heat treatment is constant, the higher the mass of the expanded graphite in the added positive electrode material layer, the higher the mass percentage X1 of the expanded graphite in the positive electrode material layer, and vice versa.

[0049] In one embodiment of the present application, the DC internal resistance of the electrochemical device at 25°C and 80% SOC for 360s at 1C discharge is 30mΩ to 60mΩ. For example, the DC internal resistance of the electrochemical device at 25°C and 80% SOC for 360s at 1C discharge can be 30mΩ, 35mΩ, 40mΩ, 45mΩ, 50mΩ, 55mΩ, 60mΩ, or a range consisting of any two of these values. The electrochemical device that meets the above characteristics has a small DC internal resistance and good rate performance, which indicates that the electrochemical device has good kinetic performance.

[0050] The second aspect of the present application provides a method for preparing the electrochemical device described in the first aspect of the present application, which includes the steps of preparing a positive electrode sheet: S1, mixing a positive electrode active material, a conductive agent, a binder, and expanded graphite in a mass ratio of (95-98): (0.7-2): (0.1-3): (0.05-1), adding a solvent and stirring evenly to obtain a positive electrode slurry, S2, applying the positive electrode slurry to one surface of the positive electrode collector, and heat treating it at a temperature range of 120°C to 350°C to obtain a positive electrode material layer; S3, repeating the above steps on the other surface of the positive electrode collector, and obtaining a positive electrode sheet through cold pressing, cutting, and welding processes. For example, the heat treatment temperature can be 120°C, 150°C, 200°C, 250°C, 300°C, 350°C, or a range consisting of any two of these values. In the present application, expanded graphite is added during the preparation of the positive electrode material layer. After being subjected to the high temperature within the above range, the expanded graphite expands longitudinally in a worm-like manner after being heated so that it drills out of the positive electrode material layer. Therefore, the expanded graphite that escapes from the positive electrode material layer leaves holes, thereby providing a transmission path for lithium ions, shortening the lithium ion diffusion distance, and reducing the lithium ion transmission resistance and polarization at the same time. Lithium ions can be quickly and evenly embedded in and escaped from the positive electrode material layer, thereby further improving the kinetic performance of the electrochemical device.

[0051] In some embodiments of the present application, before heat treatment, the mass percentage content of expanded graphite in the positive electrode material layer is X2, satisfying: 0.05% ≤ X2 < 1%. For example, X2 can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% or a range consisting of any two of the values. By regulating the mass percentage content X2 of the expanded graphite in the positive electrode material layer before heat treatment within the scope of the present application, the porosity of the positive electrode plate after heat treatment can be improved, which is beneficial to increase the lithium ion transmission rate and further improve the kinetic performance of the electrochemical device.

[0052] In some embodiments of the present application, 2≤X2 / X1≤8. For example, X2 / X1 can be 2, 3, 4, 5, 6, 7, 8, or a range consisting of any two of these values. By regulating the value of X2 / X1 within the range of the present application, it is beneficial to increase the lithium ion transfer rate, thereby further improving the kinetic performance of the electrochemical device.

[0053] In some embodiments of the present application, before the positive electrode sheet is heat treated, the density of the expanded graphite in the positive electrode material layer is 2.05 g / cm 3 Up to 2.5g / cm 3 .

[0054] In some embodiments of the present application, after the positive electrode sheet is heat treated, the density of the expanded graphite in the positive electrode material layer is 0.02 g / cm 3 Up to 0.07g / cm 3 .

[0055] In some embodiments of the present application, the density difference of the expanded graphite in the positive electrode material layer before and after the heat treatment of the positive electrode sheet is 1.98 g / cm 3 Up to 2.48g / cm 3 .

[0056] In the present application, after the positive electrode sheet is heat-treated and the expanded graphite in the positive electrode material layer is removed, the density of the expanded graphite remaining in the positive electrode material layer may be the same as or different from the density of the expanded graphite before the heat treatment.

[0057] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0058] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0059] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0060] In some embodiments of the present application, the inorganic layer includes inorganic particles and an inorganic layer binder. The present application has no particular restrictions on inorganic particles, for example, the inorganic particles may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, for example, the inorganic layer binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.

[0061] In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0062] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.

[0063] In the present application, the electrochemical device also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0064] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.

[0065] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.

[0066] In some embodiments of the present application, the negative electrode material layer may also include a negative electrode conductive agent, a negative electrode binder and a thickener. The present application has no particular restrictions on the types of negative electrode conductive agents, negative electrode binders and thickeners, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the negative electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The thickener may include, but is not limited to, at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.

[0067] The present application has no particular restriction on the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder and the thickener in the negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.

[0068] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 120 μm.

[0069] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.

[0070] Optionally, the negative electrode sheet may further include a negative electrode conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the negative electrode conductive layer, which may be a conductive layer commonly used in the art. For example, the negative electrode conductive layer includes a negative electrode conductive layer conductive agent and a negative electrode conductive layer binder. The present application has no particular restrictions on the negative electrode conductive layer conductive agent and the negative electrode conductive layer binder, and may be, for example, at least one of the above-mentioned negative electrode conductive agent and the above-mentioned negative electrode binder.

[0071] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.

[0072] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium hexafluorosilicate (LiSiF6), lithium bis(oxalatoborate) (LiBOB) and lithium difluoroborate (LiF2OB). The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.

[0073] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.

[0074] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0075] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0076] The present application does not particularly limit the type of electrochemical device, which may include any device that undergoes an electrochemical reaction. In the present application, the electrochemical device may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0077] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0078] The third aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect of the present application or the electrochemical device prepared according to the preparation method described in the second aspect of the present application.

[0079] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0080] Example

[0081] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0082] Test methods and equipment:

[0083] Test method for the mass percentage of expanded graphite X1 and X2 in the positive electrode material layer:

[0084] 1) Sample preparation: disassemble the positive electrode sheet from the lithium-ion battery, weigh the mass M1 of the positive electrode material layer, put it into a muffle furnace at 600°C and burn it for 2h to remove the binder and prepare it into a uniform powder;

[0085] 2) Preparing a suspension: dispersing the powder in N-methylpyrrolidone (NMP) to form a suspension;

[0086] 3) In this application, the expanded graphite powder is obtained by density gradient centrifugation. Since the density of the expanded graphite after heat treatment is less than the density of the conductive agent and less than the density of the positive electrode active material. In the embodiments and comparative examples of this application, the density of the expanded graphite before heat treatment is a1 = 2.2 g / cm 3 The density of the conductive agent Super P is 1.5g / cm 3 The density of lithium cobalt oxide is 5.1g / cm 3 ; The density of the expanded graphite after heat treatment is a2 = 0.05g / cm 3 The density of the conductive agent Super P and lithium cobalt oxide remains unchanged, so the upper turbid liquid is dried into powder. The powder is the expanded graphite in the positive electrode material layer after heat treatment. Its mass M2 is measured to obtain the mass M2 of the expanded graphite in the positive electrode material layer after the positive electrode plate is heat treated, X1(%) = M2 / M1×100%.

[0087] a) Pore volume: disassemble the positive electrode sheet from the lithium-ion battery, weigh the mass M1 of the positive electrode material layer, and the total volume is V1. The porosity of the positive electrode material layer is q% (the porosity of the positive electrode sheet without expanded graphite is 15%) tested by the "Porosity Test Method of Positive Electrode Material Layer", then the pore volume V2 = V1 × (q% - 15%);

[0088] b) It is known that the density of expanded graphite after heat treatment is a2 = 0.05 g / cm 3 ;

[0089] c) After the positive electrode sheet is heat treated, the mass of expanded graphite released from the positive electrode material layer is M4 = V2 × a2 = V1 ×

[0090] (q%-15%)×a2;

[0091] d)X2(%)=(M4+M2) / (M1+M4)×100%.

[0092] Porosity test method of positive electrode material layer:

[0093] 1) Sample pretreatment: disassemble the lithium-ion battery discharged at 0.2C rate to a cut-off voltage of 3.0V, clean the positive electrode sheet with DMC and place it in a fume hood to dry for 2 hours, cut the positive electrode sheet into 10mm×10mm pieces by cutting, and calculate the volume of the electrode sheet sample as V1;

[0094] 2) Place the sample in 1) in the low-pressure sample cell of the mercury intrusion instrument (model: Autopore IV9500). When starting the test, keep the pressure of the sample cell at low pressure (10 -2 kPa) to remove air from the sample;

[0095] 3) Under low pressure conditions, mercury is gradually introduced into the sample pool by controlling the valve, and mercury begins to enter the large pores in the positive electrode. The pressure range is gradually increased to 200 MPa. At this stage, mercury enters the smaller pores of the electrode, and the volume V2 of mercury intruding into the sample is recorded by the sensor;

[0096] 4) Porosity (%) = V2 / V1×100%.

[0097] Pore ​​size test method for positive electrode material layer:

[0098] 1) Sample pretreatment: The lithium-ion battery discharged at a rate of 0.2C to a cut-off voltage of 3.0V was disassembled, the positive electrode sheet was cleaned with DMC and placed in a fume hood to dry for 2 h, and then a 3 cm×3 cm positive electrode sheet was prepared by cutting.

[0099] 2) polishing the surface of the positive electrode plate by argon ion polishing technology to obtain a smooth surface of the positive electrode plate; and observing the surface of the positive electrode material layer by scanning electron microscope (SEM, model Philips XL-30), with a magnification of 10000 times;

[0100] 3) Use the test tool provided by the SEM to measure the pore size, perform statistical analysis and calculation, and obtain the average value of the pore size, which is the pore size of the positive electrode material layer.

[0101] Test method for the maximum thickness H and average pore depth h of the positive electrode material layer:

[0102] 1) Sample pretreatment: The lithium-ion battery discharged at a rate of 0.2C to a cut-off voltage of 3.0V was disassembled, the positive electrode sheet was cleaned with DMC and placed in a fume hood to dry for 2 h, and then a 3 cm×3 cm positive electrode sheet was prepared by cutting.

[0103] 2) Plasma longitudinal cutting is performed on the electrode sample along the thickness direction to obtain a flat cross section, which is characterized by SEM (model: Philips XL-30), and the magnification of the SEM is adjusted to 10,000 times. All holes in the cross section of the positive electrode are selected and measured using the test tool provided by the SEM. The average value of the hole depth is calculated as the average hole depth h;

[0104] Adjust the magnification of SEM to 10,000 times, select the position that is neither a through hole nor a non-through hole in the cross section of the positive electrode sheet sample along the thickness direction to measure the thickness, measure multiple locations, calculate the average value, and take it as the maximum thickness H of the positive electrode material layer on one side of the positive electrode sheet.

[0105] The number of through holes and non-through holes in the positive electrode material layer away from the positive electrode current collector surface per square centimeter and N and the number of through holes in the positive electrode material layer n test method:

[0106] 1) Sample pretreatment: disassemble the lithium-ion battery discharged at 0.2C rate to a cut-off voltage of 3.0V, clean the positive electrode with DMC and place it in a fume hood to dry for 2 hours;

[0107] 2) The above-mentioned electrode is processed into a 1cm×1cm grid, and the 1cm×1cm electrode area is placed under the stage of a charge coupled device (CCD) optical microscope (model DM2700M), and the focus is adjusted within the magnification range of 30 to 50 times until the through holes and non-through holes in the 1cm×1cm electrode area can be clearly seen;

[0108] 3) Calculate the number of through holes and non-through holes in the above observation area, take 32 1cm×1cm electrode areas, and calculate the average value as N. Among them, the holes that can directly observe the surface of the positive electrode collector are through holes, and their average number is calculated as n.

[0109] Single-sided coating weight of positive electrode material layer:

[0110] 1) Sample pretreatment: disassemble the lithium-ion battery discharged at 0.2C rate to a cut-off voltage of 3.0V, clean the positive electrode with DMC and place it in a fume hood to dry;

[0111] 2) Cut the positive electrode sheet in 1) to a cutting area of ​​1540.25mm 2 , and weigh it M, unit: g / 1540.25mm 2 ;

[0112] 3) Soak the positive electrode sheet in 2) in NMP and ultrasonicate for 20 mins to ensure that the positive electrode material layer is completely separated from the positive electrode current collector, and weigh the positive electrode current collector m, unit: g / 1540.25 mm 2 ;

[0113] 4) The single-sided coating weight of the positive electrode material layer is (Mm) / 2, unit: g / 1540.25mm 2 .

[0114] Compacted density of positive electrode material layer:

[0115] 1) Sample pretreatment: disassemble the lithium-ion battery discharged at 0.2C rate to a cut-off voltage of 3.0V, clean the positive electrode with DMC and place it in a fume hood to dry;

[0116] 2) Measure the thickness of the positive electrode sheet d1 μm and the thickness of the positive electrode current collector d2 μm in 1);

[0117] 3) According to the “single-sided coating weight of the positive electrode material layer” test method, the single-sided coating weight of the positive electrode material layer (g / 1540.25mm 2 ), compaction density of positive electrode material layer = single-sided coating weight × 2 × 1540.25 × 100 / ((d1-d2) / 10000), unit: g / cm 3 .

[0118] DC internal resistance test method:

[0119] 1) The test environment temperature is 25±2℃, the lithium-ion battery is charged at 1C constant current to an upper voltage of 4.5V, the battery capacity Q1 is recorded, and then the battery is discharged at 0.2C to Q2, where Q2=80%×Q1;

[0120] 2) Discharge the lithium-ion battery at 1C for 360 seconds;

[0121] 3) The voltage drop in the process of 2) is measured as △U, and the current is measured as I;

[0122] 4) The DC internal resistance of a lithium-ion battery at 25°C and 80% SOC when discharged at 1C for 360 seconds = △U / I.

[0123] Example 1

[0124] <Preparation of positive electrode sheet>

[0125] The positive electrode active material LiCoO2, expanded graphite, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.3:0.1:1.2:1.4. The conductive agent Super P is acetylene black. NMP is added as a solvent to prepare a slurry with a solid content of 75wt%. After vacuum stirring, the positive electrode slurry is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 150°C to obtain a positive electrode sheet with a single-sided positive electrode material layer. The coating weight of the positive electrode material layer is 272mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode material layer coated on both sides. After cold pressing and welding of the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 42μm and the compaction density is 4.2g / cm3 .

[0126] <Preparation of negative electrode sheet>

[0127] The negative electrode active material artificial graphite, the negative electrode binder styrene butadiene rubber, and the negative electrode conductive agent acetylene black were mixed in a mass ratio of 97.4:1.4:1.2, and deionized water was added as a solvent to prepare a slurry with a solid content of 45wt%. The negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. Among them, the thickness of the single-sided negative electrode material layer is 54.5μm and the compaction density is 1.7g / cm 3 .

[0128] <Preparation of Electrolyte>

[0129] In an environment where the water content is less than 10 ppm, dimethyl carbonate, diethyl carbonate and ethylene carbonate are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then electrolyte salt LiPF6 is added to the organic solvent and mixed evenly to obtain an electrolyte solution. The mass percentage of LiPF6 based on the mass of the electrolyte solution is 12.5%.

[0130] <Isolation film>

[0131] A porous polyethylene film with a thickness of 7 μm (provided by Celgard Company) was used as the separator.

[0132] <Preparation of lithium-ion batteries>

[0133] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film shell bag, and the water is removed at 80°C, and the prepared electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, formation, degassing, and trimming.

[0134] Example 2 to Example 4

[0135] Except for adjusting the relevant data according to Table 1, the rest is the same as Example 1. When the content of other materials except the positive electrode active material in the positive electrode material layer changes, the mass percentage of the positive electrode active material changes accordingly, and the total mass of the positive electrode material layer is 100%.

[0136] Example 5 to Example 6

[0137] Except for adjusting the content of X2 and the drying temperature and drying time of the positive electrode sheet so that the value of X2 / X1 is as shown in Table 1, the rest is the same as Example 1. When the content of other materials other than the positive electrode active material in the positive electrode material layer changes, the mass percentage of the positive electrode active material changes accordingly, and the total mass of the positive electrode material layer is 100%.

[0138] Example 7 to Example 20

[0139] Except for adjusting the relevant data according to Table 1, the rest is the same as Example 1. When the content of other materials except the positive electrode active material in the positive electrode material layer changes, the mass percentage of the positive electrode active material changes accordingly, and the total mass of the positive electrode material layer is 100%.

[0140] Comparative Example 1

[0141] Except for preparing the positive electrode sheet according to the following preparation method, the rest is the same as Example 1.

[0142] <Preparation of positive electrode sheet>

[0143] The positive electrode active material LiCoO2, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.3:1.2:1.5. The conductive agent Super P is acetylene black. NMP is added as a solvent to prepare a slurry with a solid content of 75wt%. After vacuum stirring, the positive electrode slurry is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120°C to obtain a positive electrode sheet with a single-sided positive electrode material layer. The coating weight of the positive electrode material layer is 272mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cold pressing and welding of the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 42μm, and the compaction density of the cold pressing process is 4.2g / cm 3 .

[0144] Comparative Example 2 to Comparative Example 3

[0145] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1. When the content of other materials except the positive electrode active material changes, the mass percentage of the positive electrode active material changes accordingly, and the total mass of the positive electrode material layer is 100%.

[0146] The lithium ion batteries in the embodiments and comparative examples were tested, and the performance parameters of the lithium ion batteries in the embodiments and comparative examples were obtained as shown in Table 1.

[0147]

[0148]

[0149] The total number of through holes and non-through holes per square centimeter on the surface of the positive electrode material layer away from the positive electrode current collector and the values ​​of N and n / N will affect the kinetic performance of the lithium-ion battery. From Examples 1 to 20 and Comparative Examples 1 to 3, it can be seen that the total number of through holes and non-through holes per square centimeter on the surface of the positive electrode material layer away from the positive electrode current collector and the values ​​of N and n / N are within the scope of the present application, the pore size of the positive electrode material layer is large, the porosity is high, the h / H is high, the prepared lithium-ion battery has good ion transport performance and has a low DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0150] After heat treatment, the mass percentage X1 of expanded graphite in the positive electrode material layer affects the kinetic performance of the lithium ion battery. It can be seen from Examples 1 to 4 that when the value of X1 is within the scope of the present application, the pore size of the positive electrode material layer is larger, the porosity is higher, and the h / H is higher. The prepared lithium ion battery has better ion transmission performance and has a lower DC internal resistance, indicating that the kinetic performance of the lithium ion battery can be improved. Among them, the mass percentage X1 of expanded graphite in Comparative Example 3 is larger, the pore size of the positive electrode material layer is larger, the porosity is higher, and the h / H is higher, which is not conducive to electron transmission, and the prepared lithium ion battery has a higher DC internal resistance.

[0151] The value of X2 / X1 will affect the kinetic performance of lithium-ion batteries. It can be seen from Examples 1, 5 and 6 that the value of X2 / X1 is within the scope of this application, the pore size of the positive electrode material layer is larger, the porosity is higher, the h / H is higher, the prepared lithium-ion battery has better ion transport performance and lower DC internal resistance, indicating that the kinetic performance of lithium-ion batteries can be improved.

[0152] The h / H value of the positive electrode material layer will affect the kinetic performance of the lithium-ion battery. From Examples 1, 17, and 20, it can be seen that when the h / H of the positive electrode material layer is within the scope of this application, the prepared lithium-ion battery has a lower DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0153] The mass percentage content X3 of the conductive agent will affect the kinetic performance of the lithium-ion battery. It can be seen from Example 1, Example 7 to Example 8 that the mass percentage content X3 of the conductive agent is within the scope of this application, the pore size, porosity, and h / H of the positive electrode material layer are roughly the same, and the prepared lithium-ion battery has good electronic conductivity and low DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0154] The material of the binder will affect the kinetic performance of the lithium-ion battery. It can be seen from Examples 1, 9 and 10 that the material of the binder is within the scope of this application, the pore size, porosity and h / H of the positive electrode material layer are roughly the same, and the prepared lithium-ion battery has a lower DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0155] The positive electrode active material will affect the kinetic performance of the lithium-ion battery. It can be seen from Examples 1, 11 and 12 that the positive electrode active material is within the scope of this application, the pore size, porosity and h / H of the positive electrode material layer are roughly the same, and the prepared lithium-ion battery has a lower DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0156] The single-sided coating weight of the positive electrode material layer will affect the dynamic performance of the lithium-ion battery. It can be seen from Example 1 and Example 13 to Example 16 that the single-sided coating weight of the positive electrode material layer is within the scope of this application, the pore size, porosity, and h / H of the positive electrode material layer are roughly the same, and the prepared lithium-ion battery has a lower DC internal resistance, indicating that the dynamic performance of the lithium-ion battery can be improved. Among them, compared with Example 1, the single-sided coating weight of Example 13 to Example 14 is lower, the lithium ion transmission path becomes shorter, and the DC internal resistance of the lithium-ion battery is lower; compared with Example 1, the single-sided coating weight of Example 15 to Example 16 is higher, the lithium ion transmission path becomes longer, and the DC internal resistance of the lithium-ion battery is higher.

[0157] The compaction density of the positive electrode material layer will affect the kinetic performance of the lithium-ion battery. It can be seen from Examples 1 and 17 to 20 that the compaction density of the positive electrode material layer is within the scope of this application, and the prepared lithium-ion battery has good ion transport performance and low DC internal resistance, indicating that the kinetic performance of the lithium-ion battery can be improved.

[0158] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0159] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0160] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device, comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the positive electrode material layer comprising a positive electrode active material and expanded graphite; The sum of the number of through holes and non-through holes per square centimeter on the surface of the positive electrode material layer away from the positive electrode current collector is N, and the number of through holes in the positive electrode material layer is n, satisfying: 0.4≤n / N≤0.

75.

2. The electrochemical device according to claim 1, wherein: The pore size of the positive electrode material layer is 100 μm to 200 μm.

3. The electrochemical device according to claim 1, wherein 2≤N≤12。 4. The electrochemical device according to claim 3, wherein: 6≤N≤12。 5. The electrochemical device according to claim 1, wherein The porosity of the positive electrode material layer is 20% to 35%.

6. The electrochemical device according to claim 1, wherein The maximum thickness of the positive electrode material layer is H, and the average pore depth is h, which satisfies: 0.5≤h / H≤0.

9.

7. The electrochemical device according to claim 1, wherein: The mass percentage of the expanded graphite in the positive electrode material layer is X1, 0.01%≤X1≤0.25%.

8. The electrochemical device according to claim 1, wherein The positive electrode sheet satisfies at least one of the following conditions: (1) The positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate; (2) The positive electrode material layer includes a binder, and the binder is selected from at least one of polyvinylidene fluoride, polyacrylonitrile, and polyimide.

9. The electrochemical device according to claim 1, wherein: The positive electrode sheet satisfies at least one of the following conditions: (1) The coating weight of the positive electrode material layer on one side is 200 mg / 1540.25 mm 2 Up to 600mg / 1540.25mm 2 ; (2) The compaction density of the positive electrode material layer is 3.5 g / cm 3 Up to 4.5g / cm 3 .

10. The electrochemical device according to claim 9, wherein: The positive electrode sheet satisfies at least one of the following conditions: (1) The coating weight of the positive electrode material layer on one side is 200 mg / 1540.25 mm 2 Up to 500mg / 1540.25mm 2 ; (2) The compaction density of the positive electrode material layer is 4.1 g / cm 3 Up to 4.3g / cm 3 .

11. The electrochemical device according to claim 1, wherein The electrochemical device has a DC internal resistance of 30 mΩ to 60 mΩ when discharged at 1C for 360 s at 25° C. and 80% SOC.

12. A method for preparing an electrochemical device according to any one of claims 1 to 11, comprising the steps of preparing the positive electrode sheet: S1, mixing the positive electrode active material, the conductive agent, the binder and the expanded graphite, adding a solvent and stirring to obtain a positive electrode slurry; S2, applying the positive electrode slurry on one surface of the positive electrode current collector, and subjecting the positive electrode slurry to a heat treatment at a temperature ranging from 120° C. to 350° C. to obtain the positive electrode material layer; S3, repeating the above steps on the other surface of the positive electrode current collector to obtain the positive electrode sheet through cold pressing, cutting and welding processes.

13. The preparation method according to claim 12, wherein: Before heat treatment, the mass percentage of the expanded graphite in the positive electrode material layer is X2, 0.05%≤X2≤1%.

14. An electronic device comprising the electrochemical device according to any one of claims 1 to 11 or the electrochemical device prepared by the preparation method according to any one of claims 12 to 13.